Ponseti Casting for Severe Club Foot Deformity: Are Clinical Outcomes Promising? - Mohammad Hallaj-Moghaddam; Ali Moradi; Mohammad Hosein Ebrahimzadeh; Seyed Reza Habibzadeh Shojaie (Advances in Orthopedics)
Between 2007 and 2010, a prospective study was done on 85 patients with severe idiopathic nonsyndromic clubfeet, in our center. Demographic features, severity of the deformity before and after serial casting according to Diméglio classification, and complications were assessed. The mean age of the patients was 8 days and 69% were male. The mean follow-up period was 26 months. The average number of castings used to correct the deformity was 5.7 times (range: 4 to 8). Tenotomy was performed in 76 (89.4%) of the feet. In all patients, plantigrade foot was achieved. Tenotomy occurred more in patients with higher Diméglio scores. Although patients who underwent Achilles tenotomy began to walk later than those who did not (13±7.2 versus 9.2±18), it was not significant (P=0.06). Relapse rate, at the end of follow-up, was 27.1%. Diméglio score before casting was 16±3.4 and at the end of follow-up it was 1.6±6.2. The patients with bilateral clubfeet had inferior final outcome compared to those with unilateral clubfoot. Eighty percent of parents’ were completely satisfied with their child's gait and foot appearance (94.1%). Ponseti method of manipulation and casting is a valuable technique in severe club foot as well as in common types.